Pengaruh Kebijakan Sertifikasi dan Manajemen Kinerja terhadap Peningkatan Kompetensi Pedagogik Guru di Indonesia - Annisya Muplihatin; Winengan winwngan; Hadi Kusuma Ningrat (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study examines the influence of certification policies and performance management on improving teachers’ pedagogical competence in Indonesia. Using a qualitative literature review method, the study finds that teacher certification and effective performance management positively contribute to enhancing teachers’ professionalism, teaching skills, and learning quality. Certification encourages teachers to improve their competencies, while performance management supports continuous development through supervision, coaching, and evaluation. Overall, both aspects play an important role in strengthening pedagogical competence and improving the quality of national education.